2017
DOI: 10.1002/pd.5063
|View full text |Cite
|
Sign up to set email alerts
|

Predicting postnatal renal function of prenatally detected posterior urethral valves using fetal diffusion‐weighted magnetic resonance imaging with apparent diffusion coefficient determination

Abstract: Here, it seems that diffusion-weighted magnetic resonance imaging with ADC determination could be useful in accurately evaluating fetal kidneys in PUV and predicting renal function. It may be an additional, non-invasive method when biologic and sonographic findings are inconclusive, especially in the case of oligohydramnios. Further studies are needed to confirm our data. © 2017 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…This requires antenatal assessment of renal parenchyma and amniotic fluid volume, both of which can be done with modern MR image acquisition and processing. 67,68 While Fetal MRI does not represent a gold-standard for diagnosis, it is recognised to be a useful adjunct in the evaluation of identified pathology. 69,70 Fetal MR has further prognostic use in evaluating the renal parenchyma in detail, assessing for the presence of cysts and parenchymal dysplasia, detailed in the illustrative cases below.…”
Section: Lesions Of the Kidneys And Urinary Tractmentioning
confidence: 99%
“…This requires antenatal assessment of renal parenchyma and amniotic fluid volume, both of which can be done with modern MR image acquisition and processing. 67,68 While Fetal MRI does not represent a gold-standard for diagnosis, it is recognised to be a useful adjunct in the evaluation of identified pathology. 69,70 Fetal MR has further prognostic use in evaluating the renal parenchyma in detail, assessing for the presence of cysts and parenchymal dysplasia, detailed in the illustrative cases below.…”
Section: Lesions Of the Kidneys And Urinary Tractmentioning
confidence: 99%
“…An apparent diffusion coefficient (ADC) value is calculated for each voxel within an image. Fetal kidney ADC decreases with increasing gestation, but the pattern may be quite different in urinary tract anomalies . Normally, the fetal kidney shows restricted diffusion similar to that of the mother's kidneys.…”
Section: Imaging Of the Pathologic Urinary Tractmentioning
confidence: 97%
“…Lack of a normal DWI bright signal in the renal fossae without evident renal signal elsewhere is consistent with renal agenesis rather than ectopic kidneys . It has also been suggested that DWI with ADC determination is useful for predicting renal function in the presence of posterior urethral valves …”
Section: Imaging Of the Pathologic Urinary Tractmentioning
confidence: 98%
“…27,28 The DWI sequence may be useful in defining the renal parenchyma by evaluating increased signal intensity on DWI and decreased signal on ADC maps. 29 However, the case series are small, and further studies are necessary to fully define the benefits of MRI in evaluating and managing patients with LUTO. 30 Sonographic evaluation of the posterior fossa and the spine is limited by fetal position, maternal body habitus, oligohydramnios, and ossification of the fetal skull.…”
Section: Magnetic Resonance Imaging and Fetal Surgerymentioning
confidence: 99%